1983
DOI: 10.1210/jcem-57-1-190
|View full text |Cite
|
Sign up to set email alerts
|

Sibship with 17-Ketosteroid Reductase (17-KSR) Deficiency and Hypothyroidism. Lack of Linkage of Histocompatibility Leucocyte Antigen and 17-KSR Loci*

Abstract: A family with nine children, three with male pseudohermaphroditism due to testicular deficiency of 17-ketosteroid reductase activity (17-KSR) and four with congenital hypothyroidism is presented. The three subjects with 17-KSR deficiency were raised as females until puberty, at which time they assumed a male gender role. Only one developed gynecomastia. Laparotomy on one of the three patients revealed normal epididymi and vas deferens with absence of Mullerian structures. Testicular biopsy in all three showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

1987
1987
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…Previous studies have shown normal levels of cytosolic androgen receptors in the genital skin of infant [15], pubertal and adult cases [10,[22][23], The reason for the decreased number of receptors seen in our patient is not clear. This finding may be the result of deficient androgen produc tion in both fetal and early postnatal life.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Previous studies have shown normal levels of cytosolic androgen receptors in the genital skin of infant [15], pubertal and adult cases [10,[22][23], The reason for the decreased number of receptors seen in our patient is not clear. This finding may be the result of deficient androgen produc tion in both fetal and early postnatal life.…”
Section: Discussioncontrasting
confidence: 65%
“…There is clear evidence in vitro for androgen-induced augmentation of androgen receptor binding [20]. Furthermore, there is evi dence to show age-dependent changes in androgen recep tor levels [24], We suggest that the discrepancy in the androgen receptor findings in our patient and in the majority of older patients reported elsewhere [10,22,23] may be due to a combination of this age-related change and to the increase in androgen synthesis which appears to occur in 17-ketoreductase deficiency with increasing maturity [14], Nevertheless, this hypothesis does not ex plain the difference compared to the only other study that we are aware of, of androgen receptor binding in infancy [15], except that our results were based on a whole-cell binding assay (total receptor concentration) rather than on a cytosolic receptor assay. Decreased receptor binding is sometimes observed in patients with the androgen insensitivity syndrome, but invariably associated with an altered binding affinity.…”
Section: Discussionmentioning
confidence: 50%
“…Pedigree analysis of the Arab kindred with 17-KSRD clearly shows consanguinity also suggesting an autosomal recessive inheritance of this condition (Rosler & Kohn, 1983). Sporadic cases of siblings with 17-KSRD without any family history also support this mode of inheritance (Givens et al, 1974;Saez et al, 1971;Lanes et al, 1983;Balducci et ul., 1985). To date, however, the biochemical defect has not been reported in females from the same kindred, or in obligate carrier parents, information that would confirm inheritance as autosomal recessive.…”
Section: Discussionmentioning
confidence: 82%